Variation of coefficient of friction and friction head losses along a pipe with multiple outlets - Alawee, Wissam H.; Almolhem, Yousef A.; Yusuf, Badronnisa; Mohammad, Thamer Ahmad; Dhahad, Hayder A. (MDPI, 2020)
The flow in a pipe having multiple outlets is considered as an advanced problem in hydraulic engineering; many discrepancies were found in the literature, in addition to the lack of experimental and field studies. The main goal of this study is to simulate the flow in a pipe with multiple outlets in order to examine the existing methodologies for estimation of the friction head losses, and to propose a methodology that is based on experimental data. The main physical model in this study consisted of a water supply tank, a pipe with multiple outlets having a piezometer at each outlet. Different pipe diameters were used in this study, the pipe diameters were 25.4 mm (1 in), 38.1 mm (1.5 in), 50.8 (2 in) and 76.2 mm (3 in). The inlet heads used were 1.7 m and 2.2 m. The data collected from different flow conditions were used to assess the variation in the coefficient of friction and friction head losses along the pipe length. It can be concluded that the spacing between any two successive outlets (S) and area ratio (AR = Area of outlet/Area of the main pipe) are the main factors affecting the friction head losses along the pipe. The ratio of total friction head losses along a pipe with outlets having the same properties (length (L), discharge (Q), diameter (d) and material) to a pipe without outlets and having the same properties is called the G factor. The G factor calculated using selected formulae was overestimated in comparison to the calculated G factor obtained from experimental data. For large values of S/d (spacing between outlets/diameter of main pipe), the difference between coefficient of friction in first segment (f1) and last segment (fn) of the multiple outlet pipe was noted to be minimal.